Development of coating technology using rotary pan for production of slow-release urea - Babadi, Farahnaz Eghbali (2015)
Urea fertilizer has been used for many years to supplement nutrients in growing media. Urea has the advantages of low cost and easy availability, thus touts as the most popular nitrogenous fertilizer. However, the major disadvantage of urea is its high solubility in water and its susceptibility to nitrogen losses through various pathways like leaching, ammonia volatilization, nitrification and denitrification. This adds extra cost for fertilizers manufacturer and higher concentration of urea in the soil. Currently,the use of slow-release fertilizer is a trend to reduce fertilizer consumption and to minimize environmental pollution. Slow-release nitrogenous-based fertilizer is often linked to positive characteristics such as regular release of nitrogen over a long period, reductions in nitrate leaching and reduced volatilization. However, slow-release nitrogen sources tend to be more expensive compared to other products and may lead to nitrogen release mismatch. The coating process of urea has been performed using different techniques and various materials to delay urea release. In this study, a low cost rotary pan coating technology running at room temperature was used as the coating process for urea. In the first experiment, a fractional factorial design of experiment was utilized to screen the operational parameters of rotary pan including urea particle size, proportion of coating,amount of spray water, rotation speed, pan inclination, pan loading and spray flow rate. In the second experiment; the most effective coating parameters were analyzed and optimized using a central composite design of experiments. The results of the optimized process correlated well with a second-order polynomial model with percentage of variation, R2 at 95.12%. In the next experiment, the effects of different coating formulations on the efficiency,crushing strength and morphology of the coated urea were examined. Urea fertilizer was coated using six different materials, namely, gypsum, sulfur, ground magnesium lime, kaolin clay, rice husk ash and zeolite based on the “optimal‟ parameters of rotary pan. A mixture of 25% of gypsum, 25% of sulfur and 50% zeolite gave the lowest rate of urea release with acceptable crushing strength. Six different models namely, zeroth order, first order, second order, Higuchi and Ritger & Peppas and Kopcha model were examined to understand better the relationship between coating layer and urea release mechanism. By comparing coefficient of determination (R2) of models, the Ritger & Peppas model provided the highest R2 value (≈ 0.93) for final coating formulation. The efficiency of gypsum-sulfur-zeolite (25/25/50%) coated urea was improved further where microcrystalline wax and polyol was experimented as a sealant. The efficiency of gypsum-sulfur-zeolite coated urea sealed by 3% of microcrystalline wax improved to around 56% while the efficiency of commercial sulfur coated urea is about 65%. This indicates the potential of gypsum-sulfur-zeolite coated urea produced in a room temperature process to be commercialized and used as a slow released nitrogen fertilizer.